Critical knowledge transfer : tools for managing your company's deep smarts - Leonard-Barton, Dorothy, 1942-; Swap, Walter C.; Barton, Gavin (Harvard Business Review Press, 2015)
"Addressing the critical issue of knowledge transfer within an organization, this book offers practical advice on how to structure the transition of documented information and the even more valuable non-documented knowledge that outgoing staffers have-before it leaves with them. Whether a result of a retirement, an acquisition, promotions, transfers, or layoffs-all organizations have lost what these authors call "deep smarts" when workers leave. Now, Dorothy Leonard and Walter Swap, coauthors of the popular Deep Smarts, and their coauthor Gavin Barton offer a solution. The trio has constructed a new approach that not only helps organizations put in place the structures and practices to pass along knowledge from expert to successor, but also identifies tacit knowledge-knowledge that is largely undocumented and lives inside of people's heads. Based on theory and research, this book offers a variety of examples, tools, and templates to take action before essential knowledge disappears"--Resumé vydavatele